Influência da granulometria do açúcar na textura e cor de biscoitos rosca sabor leite - Pieta, Adriana (2015)
The texture and color influence the acquisition, consumption, acceptance and preference biscuits. Some ingredients and stages of process can directly influence these parameters. Sugar is one of the main ingredients used in the formulations biscuits, and the crystal size an important factor in the mass performance and consequently to the texture and color of the product. Having in view that the movement of the sugar in the food industry is carried out usually by pneumatic transport, and the crystals are broken by changing the particle size and consequently interfering with the characteristics of the product. In this context, the objective of this study was to evaluate the influence of pneumatic conveying in particle size and color of crystal sugar and consequent changes in mass behavior and parameters texture and color of thread biscuits flavored milk. For such, particle size and color of crystal sugar analyzes were conducted, as well as the dough analysis and biscuits prepared. The sugar was obtained from three different suppliers, coded as A, B and C, and has been applied in production of dough and biscuits flavored milk thread, in two conditions: before the pneumatic transport (BPT) and after being subjected to pneumatic transport (APT), totaling six different productions of dough and biscuits. All the other ingredients and process conditions were maintained without change in all productions. Through the analysis of particle size was determined the value of mean aperture of sugar crystals and the colorimetric evaluation allowed us to determine the values of color ranges L, a * and b * (Cielab) of sugar. The rheological behavior of cookie dough was evaluated using analysis of consistency stability and hardness. The biscuits thread flavor milk have been subjected to instrumental and sensory analysis (descriptive and affective tests), which were evaluated texture (hardness and fracturability) and color (L, a * and b *). The particle size distribution in the samples of sugar BPT was significantly higher (p< 0.05) than in samples of APT. On the other hand, the analysis of color in the samples of sugar BPT showed brightness lower than in APT (p< 0.05).The hardness of the dough was higher (p <0.05) in samples where the Sugar APT was applied. The biscuit texture (hardness and fracturability) sugar BPT were significantly lower than those produced with APT sugar. The product color APT sugar was higher (p <0.05) in the product with sugar ATP. The PCA showed correlation between instrumental and sensory analysis. According to the results obtained, it was observed that the pneumatic transport directly influences the size and color of sugar, as well as the texture and color of the final product. Thus, it is concluded that the use of crystal sugar submitted to pneumatic transport (APT) in the production of biscuits milk flavor results in products darker, and with greater hardness.